1968
DOI: 10.2466/pr0.1968.22.3c.1137
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Study of Some Correlates of Birth Order

Abstract: Summa7y.-The purpose of the present study was to test the cross-culcural validity of the relacionship found in Western samples between birth order and college attendance, volucteering behavior, and level of academic achievement. Information concerning birth order and family size was obtained on three subsamples: ( a ) 200 freshman Arab students, ( b ) 97 Arab undergraduates, and (c) 45 Arab undergradcates placed o n the Dean's Honor List. Ss in samples ( b ) and ( c ) were asked whether they would volunteer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Most of the findings of the relationship between birth order and academic achievement have been based primarily on Western samples. Notwithstanding this situation and with the exception of few studies (Diab & Prothro, 1968), the limited cross-cultural studies that have been done on birth order and academic achievement support the findings from Western samples (Munroe & Munroe, 1971;Stevenson, Lucke, Lee, & Stigler, 1987;Cherian, 1990). Cherian's study (1990) of primary schoolchildren in the Transkei province of South Africa showed that irrespective of the parental socioeconomic status, the later the child's birth order, the lower the academic achievement.…”
mentioning
confidence: 85%
“…Most of the findings of the relationship between birth order and academic achievement have been based primarily on Western samples. Notwithstanding this situation and with the exception of few studies (Diab & Prothro, 1968), the limited cross-cultural studies that have been done on birth order and academic achievement support the findings from Western samples (Munroe & Munroe, 1971;Stevenson, Lucke, Lee, & Stigler, 1987;Cherian, 1990). Cherian's study (1990) of primary schoolchildren in the Transkei province of South Africa showed that irrespective of the parental socioeconomic status, the later the child's birth order, the lower the academic achievement.…”
mentioning
confidence: 85%
“…Despite 14 years of anarchy, a considerable amount of theoretical (e.g., Diab & Prothro, 1957; Keehn, 1959; Melikian & Prothro, 1955; Prothro, 1961; Saigh, in press-a; Walker, 1986) and applied (e.g., Saigh, 1987a, 1987c) psychological research has eminated in Lebanon. In the main, school psychology research has been prompted by academic interest, requests from schools and agencies, and the ever-present need to provide services for school children who were affected by the hostilities.…”
mentioning
confidence: 99%
“…In the same year, a study appeared by Diab and Prothro (1968) of Arab undergraduates at the American University of Beirut, in which they found no overrepresentation of students, regardless of family size. Even controlling for whether the student was an "honor" or a "regular" student, no overrepresentation appeared.…”
Section: Cross-cultural Studies Of Birth Ordermentioning
confidence: 98%
“…Even controlling for whether the student was an "honor" or a "regular" student, no overrepresentation appeared. Diab andProthro (1968, p. 1141) conclude:…”
Section: Cross-cultural Studies Of Birth Ordermentioning
confidence: 99%